2004
DOI: 10.1081/prg-200030860
|View full text |Cite
|
Sign up to set email alerts
|

Intraplatelet Cyclic Guanosine‐3′,5′‐Monophosphate Levels During Pregnancy and Preeclampsia

Abstract: The results of this study in a high-risk Andean population demonstrated that intraplatelet cyclic guanosine-3',5'-monophosphate levels are decreased during preeclampsia compared to normal pregnancy, suggesting a lack in action of nitric oxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Although this is in agreement with our previous observations [12][13][14][15], the reported levels of NO in relation to pre-eclampsia are contradictory [16], which is probably due to differences in the measurement methods and/or the metabolite analyzed. Nevertheless, there is agreement that pre-eclampsia is associated with altered NO production and/or activity.…”
Section: Discussionsupporting
confidence: 41%
“…Although this is in agreement with our previous observations [12][13][14][15], the reported levels of NO in relation to pre-eclampsia are contradictory [16], which is probably due to differences in the measurement methods and/or the metabolite analyzed. Nevertheless, there is agreement that pre-eclampsia is associated with altered NO production and/or activity.…”
Section: Discussionsupporting
confidence: 41%
“…In two recent studies based on the RIETE (Registro Informatizado de Enfermedad TromboEmbó lica) registry, high D-dimer [7] and low platelet count [8] in cancer patients with venous thromboembolism (VTE) at referral were found to be predicting factors of a worse clinical outcome. As elevated D-dimer and thrombocytopenia are two components of the diagnosis of DIC, we assumed that the occurrence of DIC in cancer patients with VTE would lead to an unfavorable outcome.…”
mentioning
confidence: 99%
“…More than 10 years ago, Lopez-Jaramillo et al [28] reported that hydralazine infusion in preeclamptic women was related to an increase in plasma and urinary cGMP levels, suggesting that the drug might improve endothelial cell NO production. However, our group found that although plasma NO levels were similar among normal and preeclamptic women, intraplatelet cGMP levels were lower in those with preeclampsia [13]. This suggests that during preeclampsia NO action rather than its production is abnormal.…”
Section: Discussionmentioning
confidence: 88%
“…In other words preterm preeclamptic women seem to have responded better to hydralazine, situation evidenced by higher plasma NO levels. Given that preeclampsia is characterized by free radical production [30], it could be possible that hydralazine might reduce oxidative stress and favor that equal amounts of NO be enough to stimulate soluble guanylate cyclase (GC) [13]. The final consequence of this action would be vascular dilatation and blood pressure decrease, however with different secretion patterns depending on gestational age.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation